2010
DOI: 10.1021/jp108550z
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Insights into the Mechanism of the Nucleophilic Addition of Water and Methanol to Dicyanonitrosomethanide

Abstract: In this work the nucleophilic addition of water and methanol to the dicyanonitrosomethanide anion (dcnm, [C(CN)(2)(NO)](-)) in the absence of the usual transition metal promoters was investigated. Experimentally it was shown that a quantitative conversion of the dcnm anion to carbamoylcyanonitrosomethanide (ccnm, [C(CN)(CONH(2))(NO)](-)) by the addition of 1 equiv of water to a nitrile group is complete in 48 h at 100 °C, or in 1.5 h at 150 °C when the reaction is conducted in a microwave reactor. Attempts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 82 publications
(165 reference statements)
0
13
0
Order By: Relevance
“…: The dcnm anion in [Ln(dcnm) 6 ] 3− has been observed to undergo nucleophilic addition of water to form the carbamoylcyanonitrosomethanide anion when stored under ambient conditions for one year 26b. 30 Therefore, if [Ln(dcnm) 6 ] 3− ‐containing complexes are to be stored for a long period, it is recommended that an inert atmosphere is used.…”
Section: Methodsmentioning
confidence: 99%
“…: The dcnm anion in [Ln(dcnm) 6 ] 3− has been observed to undergo nucleophilic addition of water to form the carbamoylcyanonitrosomethanide anion when stored under ambient conditions for one year 26b. 30 Therefore, if [Ln(dcnm) 6 ] 3− ‐containing complexes are to be stored for a long period, it is recommended that an inert atmosphere is used.…”
Section: Methodsmentioning
confidence: 99%
“…1). It should be noted that formation of ccnm proceeds in the presence of a transition metal and under heating of an aqueous reaction solution containing dcnm (Vitushkina et al, 2017;Izgorodina et al, 2010).…”
Section: Ir Spectroscopymentioning
confidence: 99%
“…Ccnm can also coordinate in a monodentate manner, either in the oxime form, when it is coordinated via the oxime O atom in a trans-anti configuration to transition metals, such as Sn IV (Gerasimchuk et al, 2007), Sb V (Domasevitch et al, 2000) and Te IV (Domasevitch et al, 1996), or in the nitrile form, when it is coordinated via the nitrile N atom, as in the [Cu(ccnm) 4 ] 2À complex anion, in which two ccnm ligands are coordinated via the nitrile N atoms, while the other two are coordinated in a chelating manner in the nitroso form (Chesman et al, 2010). Finally, ccnm exists as a free anion balanced by simple or complex cations (Domashevskaya et al, 1989;Gerasimchuk et al, 2010;Izgorodina et al, 2010;Janikowski et al, 2013;Fonari et al, 2005).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…According to Izgorodina et al who studied nucleophilic addition of water and methanol to dcnm in the absence of transition metals [15], the water addition to the cyano group was found to go through three distinct transition states: (1) the transfer of a proton from a water molecule to the cyano group, (2) the subsequent attack of the generated hydroxide anion on the carbon atom of the same cyano group, and (3) during its coordination to a transition metal, to form acnm anion. On the other hand, the authors found that the methanol addition to the cyano group proceeds through two transition states.…”
Section: Introductionmentioning
confidence: 99%